2006
DOI: 10.1128/iai.74.4.2022-2030.2006
|View full text |Cite
|
Sign up to set email alerts
|

Active Cytotoxic Necrotizing Factor 1 Associated with Outer Membrane Vesicles from Uropathogenic Escherichia coli

Abstract: Cytotoxic necrotizing factor type 1 (CNF1) is one of the virulence factors produced by uropathogenic Escherichia coli (UPEC). How this toxin is translocated from the bacterial cytoplasm to the surrounding environment is not well understood. Our data suggest that CNF1 may be regarded as a secreted protein, since it could be detected in culture supernatants. Furthermore, we found that CNF1 was tightly associated to outer membrane vesicles, suggesting that such vesicles play a role in the secretion of this protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 37 publications
(31 reference statements)
3
55
1
Order By: Relevance
“…Considering the different destructive enzyme activities, we also analyzed the cytopathic effects of OMVs on human alveolar epithelial cells and the protozoan host A. castellanii. However, unlike OMVs of other species (9,47,79), L. pneumophila OMVs were not cytotoxic or cytolytic. In agreement with the previous observation that L. pneumophila-free culture supernatants do not induce apoptosis (35), we did not observe OMV-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…Considering the different destructive enzyme activities, we also analyzed the cytopathic effects of OMVs on human alveolar epithelial cells and the protozoan host A. castellanii. However, unlike OMVs of other species (9,47,79), L. pneumophila OMVs were not cytotoxic or cytolytic. In agreement with the previous observation that L. pneumophila-free culture supernatants do not induce apoptosis (35), we did not observe OMV-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have shown that CNF1 from uropathogenic E. coli strains J96 and CP9 is transported to the culture supernatant in a complex with outer membrane vesicles (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…No typical signal peptide is found in the CNF1 sequence. A previous study by Kouokam et al showed that CNF1 is tightly associated with outer membrane vesicles (18). Outer membrane vesicles from a number of bacterial species have been found to contain virulence factors, exhibit immunomodulatory effects, and adhere to and intoxicate host cells (20).…”
mentioning
confidence: 99%
“…Via MVs, bacteria can expose host cells to relatively high concentrations of toxins and additional virulence factors without the requirement of a close contact between the bacterial and target mammalian cells (2)(3)(4)(5)(6)(7)(8)(9). MVs have also several defensive functions, including a role in antimicrobial peptide resistance (6,10).…”
mentioning
confidence: 99%